Biocompatible and Na+-sensitive thin-film transistor for biological fluid sensing. Issue 1 (31st December 2019) - Ito, Kensuke; Satake, Hiroto; Mori, Yuto; Tseng, Alex C.; Sakata, Toshiya
ABSTRACT: In this study, we develop a Na + -sensitive thin-film transistor (TFT) for a biocompatible ion sensor and investigate its cytotoxicity. A transparent amorphous oxide semiconductor composed of amorphous In–Ga–Zn–oxide (a-InGaZnO) is utilized as a channel of the Na + -sensitive TFT, which includes an indium tin oxide (ITO) film as the source and drain electrodes and a Ta2 O5 thin-film gate, onto which a Na + -sensitive membrane is coated. As one of the Na + -sensitive membranes, the polyvinyl chloride (PVC) membrane with bis(12-crown-4) as the ionophore used on the TFT sensors shows good sensitivity and selectivity to changes in Na + concentration but has high cytotoxicity owing to the leaching of its plasticizer to the solution; the plasticizer is added to solve and entrap the ionophore in the PVC membrane. On the other hand, a plasticizer-free Na + -sensitive membrane, the fluoropolysilicone (FPS) membrane with the bis(12-crown-4) ionophore, also reduces cell viability owing to the leaching of the ionophore. However, the FPS membrane with calix[4]arene as the ionophore on the gate of TFT sensors exhibits not only favorable electrical properties but also the lack of cytotoxicity. Thus, considering structural flexibility of TFTs, a platform based on TFT sensors coated with the Na + -sensitive FPS membrane containing calix[4]arene is suitable as a biocompatible Na + sensing system for the continuous monitoring of ionic components in biological fluids such as sweat and tears. GRAPHICAL ABSTRACT: uf0001